Optimization of Radioisotope Production at Rsg-Gas Reactor Using Deterministic Method - Pinem, S; Susilo, J; Tukiran, -; Sembiring, T.M. (LIPI Press, 2012)
RSG-GAS is a research reactor operated for radioisotope production, material testing, research and development and also industry and university needs. The radioisotope productions are Mo-99/Tc-99m, TeO2, Iridium, Sm2O3, Gd2O3, MoO3 and others which are needed for hospital and industry. To meet all demand, optimization of irradiation has been done for increasing the target irradiation in the core so that the utilization of RSG-GAS core is also increasing. This is important to be done because the target insertion to the core will change the core characteristic and can disturb the reactor operation safety. This paper will analyz the infl uence of each target insertion and also combination of the targets insertion to the core while considering the reactor operation safety factor. The calculation of the optimization was done by a deterministic method using Standard Reactor Analysis Code (SRAC) computer code. Meanwhile the determination of optimum target was done by analyzing the infl uence ofchanges in the reactivity and radial power peak factor due to the insertion of the target in the core. Based on the calculation the number of maximum target insertion for fi ssion product molybdenum-low enrichment uranium (FPM-LEU) to get Mo-99/Tc-99m in all irradiation positions has been achieved. The E-4 and G-7 are the best core grid positions for the FPM-LEU target with the maximum mass of 21 g. Beside that, several data for calculation of TeO2, Iridium, Sm2O3, Gd2O3, MoO3, targets with different numbers and also combination of all targets have been achieved as well. Research works is ready to be applied in the management of irradiation target for optimum radioisotope production in the RSG-GAS reactor.